Morbidity and Mortality Related to COVID-19 among HIV Infected Individuals in Selected ART Sites of Kathmandu Valley (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2023)
Introduction: HIV control programme is one of the priority program of the government of Nepal. COVID-19 pandemic caused major disruptions in the implementation of health services and; diverting most of the resources and efforts to contain the COVID-19 pandemic. It also fueled the underachievement of activities of health programmes, including achievement of national HIV programme. The objectives of this study was to determine the morbidity and mortality of COVID-19 among people living with HIV (PLHIV) in selected antiretroviral therapy (ART) sites of Kathmandu valley.Methodology: A cross-sectional survey was conducted in 7 selected ART sites of Kathmandu valley using mixed methods for data collection. The sample size for the study was 388 PLHIV who were tested for COVID-19. Further, ART focal persons of the sites and key informants were interviewed on response activities of the national HIV programme during pandemics.Results: Prevalence of COVID-19 among PLHIV was 12.1% and case fatality rate was 4.2%. 7.5% participants had to cancel ART appointment due to lock down whereas 4.4% had faced the shortage of diagnostics and drugs for treatment. Majority of PLHIV (86.6%) had received multiple months dispensing of ART drugs during pandemics. PLHIV received treatment services easily whereas trainings, meetings and prevention related activities were hampered due to restriction in movement and gathering.Conclusion: It is important to focus on prevention of spread of COVID-19 among PLHIV. Uninterrupted access to ART and preventive services should be provided to PLHIV in a time of such pandemic.